MERANCANG TEMA DAN DIMENSI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) - Riswakhyuningsih, Tri (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2024)
The purpose of the study was to provide an overview of the dimensions and themes of the Pancasila student profile strengthening project (P5). The study was conducted using a descriptive qualitative method. The study was conducted at SMP Negeri 2 Subah in the 2022/2023 and 2023/2024 academic years. Data were collected using observation and documentation techniques. Data analysis was carried out using triangulation techniques. Conclusions were drawn by combining data from observations, documentation and from a theoretical perspective. SMP Negeri 2 Subah in the 2022/2023 academic year implemented 3 projects: the theme of local wisdom with the dimensions of faith, devotion to God Almighty, and noble morals; the theme of the voice of democracy with the dimensions of faith, devotion to God Almighty, and noble morals and mutual cooperation; the theme of building souls and bodies with the dimensions of faith, devotion to God Almighty, and noble morals and mutual cooperation. In the 2023/2024 academic year, 3 projects will be implemented: the theme of building souls and bodies with the dimensions of faith, devotion to God Almighty, and noble morals and mutual cooperation; the theme of Bhinneka Tunggal Ika with the dimension of global diversity; the theme of local wisdom with the dimensions of faith, devotion to God Almighty, and noble morals. Keywords: Dimensions, Themes, Pancasila Student Profile, Project for Strengthening the Pancasila Student Profile.